Ecological Legal Politics in Indonesia: Criticism of Muhammadiyah Jurisprudence in the Reformation Era - Wahdini, Muhammad; Jubba, Hasse; Kamsi, Kamsi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
: In the reform era, there was a transformation of the legal products of the Tarjih Muhammadiyah Council from monodisciplinary to multidisciplinary. One of the new products is fiqh which carries the concept of responsive fiqh. The issue of ecological politics in Indonesia is the dominant issue responded to. This research seeks to reveal the shift in the concept of fiqh muhammadiyah from monodisciplinary to multidisciplinary and criticalism fiqh muhammadiyah respond to the political constellation of ecological law in Indonesia in the reform era. The research uses normative legal research methods with a political approach to law. Data was collected through literature research. The results of this study indicate that Muhammadiyah jurisprudence is a new paradigm of responsive jurisprudence that is in line with the spirit of tajdid and ijtihad. The factor of the shift in the legal products of the Tarjih Assembly is largely determined by the role of the chairman of the Tarjih Assembly itself. Of the many fiqh products issued by the Tarjih Assembly, this study highlights Muhammadiyah fiqh products related to ecology. First, water fiqh responds to the alarming and global water crisis. In addition, water fiqh is also the basis for Muhammadiyah to conduct a judicial review of Law No. 7 of 2004 concerning Water Resources (SDA) which was granted by the Constitutional Court, in this context there is accommodation of water fiqh in ecological politics in Indonesia. Second, disaster jurisprudence responds more to social problems that are also connected to ecological problems in the disaster sector and there is no contestation or accommodation in the context of ecological legal politics. Third, Agrarian Jurisprudence responds to various agrarian problems in Indonesia such as food self-sufficiency, environmental damage, agrarian conflicts, indigenous peoples, and housing and access to public space. So that in this Fikih there is contestation with state policies in ecological politics. so that Muhammadiyah Fikih takes a role in efforts to realize a democratic political configuration that seeks to contribute fully and egalitarian to actively influence government policies.